Indonesia's National Defense Resilience during Covid-19: Key Lessons - Sarjito, Aris; Sutawidjaya, Ahmad Hidayat (Journal of Ecohumanism, 2024)
The COVID-19 pandemic tested national defense systems worldwide, including Indonesia's. This research aims to evaluate the resilience of Indonesia's National Defense System amid the global health crisis, focusing on the effectiveness of the Indonesian National Armed Forces (TNI) in managing logistical challenges, key factors influencing interagency coordination, and the role of technological innovation. Utilizing a qualitative research method based on secondary data, the study analyzes reports, government documents, and academic literature to gather comprehensive insights. Findings reveal that the TNI effectively utilized its disaster response experience to establish robust logistical operations, despite facing supply chain disruptions and geographical challenges. Effective interagency coordination was facilitated by clear roles, communication channels, and collaborative efforts, although bureaucratic hurdles occasionally hindered efficiency. Technological innovations, including digital surveillance, data management, and secure communication platforms, significantly enhanced operational effectiveness and resilience. This research offers a novel perspective by integrating multiple facets of the defense response, highlighting the interplay between logistics, coordination, and technology. The insights gained can inform strategies to strengthen national defense capabilities in future crises.